HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG PLASENTA PREVIA DENGAN KEJADIAN PLASENTA PREVIA DI PUSKESMAS PADANGMATINGGI KOTA PADANGSIDIMPUAN TAHUN 2023 - Hummaira Hutagaol; Yeni Fitri Wahyuni (Universitas Prima Indonesia, 2023)
Placenta previa is a condition in which the placenta implants in an abnormal place, namely in the lower segment of the uterus so that it covers part or all of the opening of the birth canal (internal uterine ostium) and therefore the lowest part is often constrained from entering the pelvic inlet or causing fetal abnormalities in the uterus. This study aims to determine the relationship between knowledge and the incidence of Placenta Previa at Padangmatinggi health center, Padangsidimpuan city This research method is correlation. The population in this study were all 34 mothers, with a total sample of 34 respondents, taken by total sampling. Data collection was carried out by interviewing using a questionnaire then presented in the form of frequency distribution tables and cross tables. The results of this study indicate that the majority of respondents have the type of work as housewives (IRT) as many as 22 respondents (64.7%), have a low level of education, namely elementary or junior high school as many as 22 respondents (64.7%). There is no relationship between knowledge and Placenta Previa with a value of p = 0.764 (p> 0.05). It is recommended that pregnant women in the Padangmatinggi health center, Padangsidimpuan city work area always routinely have their pregnancies checked at the nearest health care facility to avoid placenta previa. Keywords: Knowledge, Placenta Previa